Characteristic Modes of Slotted Planar Antennas - Mohamed Mohamed-Hicho, Nora (2017)
In this paper, a modal analysis of a slot inserted in a finite ground plane is presented, giving physical understanding of its radiation behavior and the interaction effects between the slot and the plane. The Theory of Characteristic Modes (TCM) reveals that for the case of slotted planar antennas the modes of the slot do not appear as independent modes. This paper also shows that the slot resonance fixes the upper frequency of the excited modes in the combined structure formed by the slot and the finite plate. Moreover, the modal analysis demonstrates that the radiation pattern stability and the radiation bandwidth of the slot antenna are directly related with the size of the finite ground plane. The conclusions reached with the application of TCM can be employed to optimize the geometry and the size of the finite plate in order to prevent the excitation of non-desired modes.